Peningkatan Pengetahuan Masyarakat tentang Mitos dan Fakta Diabetes Melitus serta Diet Seimbang Penderita Diabetes Melitus - Sunarti Sunarti; Rochana Ruliyandari; Emanuel Depa Chrisnandy; Maharani Nusara Ardhi; Candra Puspitasari; Renni Renni; Arihni Arihatal Jannah; Noernahar Septisari Usman; Veronica Sukardi Jaya; Ratnawati Ratnawati; Jumaiah Jumaiah (Universitas Teuku Umar, 2023)
Community service activities are a forum for sharing information to increase public knowledge. This community service is conducted online through seminars using the Zoom meeting application with the theme